A novel approach for optimal sizing of stand-alone solar PV systems with power quality considerations. (January 2023) - Hassan, Aakash; Bass, Octavian; Al-Abdeli, Yasir M.; Masek, Martin; Masoum, Mohammad A.S.
Highlights: Optimal sizing of stand-alone solar PV systems with power quality constraints. Performing transient simulations of detailed system model under varying conditions. Non-optimal system parameters may cause inadmissible system voltages and harmonics. Initial capital cost is marginally higher compared to conventional approach. Proposed approach can help in designing more reliable and cost-effective PV systems. Abstract: Designing reliable and cost-effective solar PV systems with compliance to national and international power quality standards is critical for their economical, efficient, and safe operation. The conventional approaches currently being used to optimally size the solar PV systems generally ignore power quality criteria during the initial design phase. This paper fills this gap by presenting a novel Genetic Algorithm (GA) based strategy to design a stand-alone solar PV system featuring optimal system size with conformance to power quality standards. MATLAB/Simulink environment was used to develop a detailed model of solar PV system, including a robust control mechanism for maximum power point tracking, battery bi-directional control, and inverter output control. An optimisation algorithm based on the single-objective GA was then designed to find the optimal PV array size, battery capacity, and the values of harmonic filter components so that the total investment cost is minimised and load demand as well as power quality criteria over the studied period are satisfied. The simulation results, corroborated with insightful discussions demonstrate that ignoring power quality criteria by selecting improper non-optimal system parameters can lead to inadmissible voltages and THD levels in the system. In contrast, the proposed design strategy can successfully devise a solar PV system that is optimally sized and complies with power quality standards.